Need of procedure guides for ultrasound applications in obstetrics and gynecology - Zavala Coca, Carlos (2015)
In sanitary services, medical act and procedures are main processes that influence persons’ health. Health care requires a series of clinical procedures based on scientific criteria, diagnosis and treatment determination and standardization so as to strenghten medical act, adequate use of resources and improving health providing quality.